An Analysis of Classroom Activities Pursuant to Effective Techniques Teaching English in Integrated Vocational Schools - Agustin, Heli; Noviyenty, Leffi; Utami, Henny Septia (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2019)
The objective of this research are to describe classroom activities pursuant to effective techniques teaching English in integrated vocational schools, and to investigate classroom activities pursuant to effective techniques teaching English in integrated vocational schools at Islamic integrated Rabbi Radhiyyahand vocational high school Islamic integrated KhoiruUmmah in CurupRejangLebong. The design of this research is descriptive qualitative. The subject of this research were two teachers who teach English in Islamic integrated vocational schools. In collecting the date, the researcher used the following techniques: checklist observation and interview. There are some instruments which the researcher used forcollecting the data, consist of: notes and interview guidance. The notes was used to find the techniques the teachers used, the classroom activities the teacher used, and identify the classroom activities that pursuant to techniques suit the elements of effective teaching, and the interview guidelines was used to find the technique the teachers used based on the theory of elements of effective teaching. In analyzing the data,the steps were data managing, description, and interpreting. Theresult from notes and interview showed that the techniques and classroom activities the teacher used and all techniques and classroom activities pursuant with element of effective teaching. The elements of effective teaching consisted of academic learning time, use of positive reinforcement, cues and feedback, cooperative learning activities, classroom atmosphere, high order questioning, direct instruction, and indirect teaching.